Sequencing and characterization of complete mitogenome DNA of Rasbora tornieri (Cypriniformes: Cyprinidae: Rasbora) and its evolutionary significance - Chung, Hung Hui; Cynthia Keranti, Kamar; Kit, Leonard Whye Lim; Jill Sela, Roja; Yunshi, Liao; Lam, Tommy Tsan-Yuk; Chong, Yee Ling (Springer, 2020)
The yellowtail rasbora (Rasbora tornieri) is a miniature ray-finned fish categorized under the genus Rasbora in the family of Cyprinidae. In this study, a complete mitogenome sequence of R. tornieri was sequenced using four primers targeting two halves of the mitogenome with overlapping flanking regions. The size of mitogenome was 16,573 bp, housing 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes and a putative control region. Identical gene organization was detected between this species and other members of Rasbora genus. The heavy strand encompassed 28 genes while the light strand accommodated the other nine genes. Most protein-coding genes execute ATG as start codon, excluding COI and ND3 genes, which utilized GTG instead. The central conserved sequence blocks (CSB-E, CSB-F and CSB-D), variable sequence blocks (CSB-1, CSB-3 and CSB-2) as well as the terminal associated sequence (TAS) were conserved within the control region. The maximum likelihood phylogenetic family tree revealed the divergence of R. tornieri from the basal region of the Rasbora clade, where its evolutionary relationships with other Rasbora members are poorly resolved as indicated by the low bootstrap values. This work acts as window for further population genetics and molecular evolution studies of Rasbora genus in future.